Does green public procurement trigger environmental innovations? - Bastian Krieger; Vera Zipperer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Green public procurement has gained high political priority and is argued to be an effective demand-side policy to trigger environmental innovations. Its implementation usually takes the form of environmental award selection criteria in public procurement tenders. However, there is no direct or broad empirical evidence on its innovation impact. There are even doubts about its effectiveness as an innovation policy tool, as it does not require innovations as part of its contracts and might only influence the selection of awardees in public procurement tenders. We construct a novel firm-level dataset to investigate the effect of winning green public procurement awards on firms' introduction of environmental innovations. Employing cross-sectional difference-in-differences methods, we find that winning green public procurement awards increases a firm's probability of introducing more environmentally friendly products on average by 20 percentage points. We show that this effect is driven by small and medium-sized firms and is not significant for larger firms. There is no significant effect on the introduction of more environmentally friendly processes.
Keywords: H57; O38; Q55; Q58; 330; Green Public Procurement; Environmental Innovation; Demand Pull